Redefining the Role of Religion in Contemporary Society: Pope Francis and Sheikh Ahmad Muhammad al-Tayyeb - Setyawan, Heri (JSW (Jurnal Sosiologi Walisongo), 2019)
This paper discusses the position of religion in contemporary society by examining the religious thoughts of two prominent religious leaders: Pope Francis from the Catholic Church and Sheikh Ahmad Muhammad al-Tayyeb from Al-Azhar University, Egypt. The meeting between Pope Francis and Sheikh Ahmad Muhammad al-Tayyeb in Abu Dhabi (February 2019) is a starting point for understanding the process by which the two religious leaders redefined the role of religion in society. Moreover, their responses to contemporary social issues such as terrorism, ecological crisis, war, and social injustices also show how they redefined the role of religion. While each religious leader formulates theological account into its religious tradition, it is obvious that the role of religion for social transformation and humanity is shown to be the central concern of the two religious’ leaders. The two religious traditions go further to put religion as a fundamental agent for society transformation.